Phyto-Molecules Utilised in Malaria Therapy: A Review (International Journal of Innovative Research in Computer Science & Technology, 2022)
Malaria is one of the most lethal tropical  illnesses known to man, and it's becoming worse because  to an increase in drug resistance in the malaria-causing  protozoan to conventional treatments. There are many  species of the protozoan falciparum which causes various  types of malaria. Several, synthetic, semisynthetic & natural origin compounds having anti-malarial property  has been commercialized. Some of them are as follows:  chloroquine is a quinine derivative whereas artesunate  having sesquiterpene lactone core is derived from  artemisinin that is isolated from Artemisia annua L.  Though the artemesinin based combination therapy  (ACT) has showed excellent results however, the rising  cases of drug resistance is now making the researchers to  search for more novel therapies. In this review paper, the  life cycle of a malarial protozoan, the current artemesinin  combination therapy and the other phyto-molecules  having anti-malarial activity has been briefed upon. One  can believe that the discovery of novel phyto-molecules  having would lead to a much safer, effective and cheaper  mode of treatment of malaria.
Keywords: Anopheles Mosquitos; Artemesinin; Artemesinin Based Combination Therapy (ACT); Malaria; Falciparum; Phyto-Molecules